2009
DOI: 10.1038/nrmicro2147
|View full text |Cite
|
Sign up to set email alerts
|

Coronaviruses post-SARS: update on replication and pathogenesis

Abstract: While coronaviruses were first identified nearly 60 years ago, they received notoriety in 2003 when one of their members was identified as the etiological agent of the Severe Acute Respiratory Syndrome (SARS-CoV) 1. Previously these viruses were known to be important agents of respiratory and enteric infections of domestic and companion animals and to cause approximately 15% of all cases of the common cold. This Review focuses on recent advances in our understanding of the mechanisms of coronavirus replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
1,641
0
48

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,567 publications
(1,699 citation statements)
references
References 142 publications
(170 reference statements)
10
1,641
0
48
Order By: Relevance
“…Among these are the proteolytic activities endowed by nsp3 and nsp5, required to mature pp1a and pp1ab polyproteins into individual non-structural proteins (11,12); the RNA-dependent RNA polymerase by nsp12, and a putative RNA primase, nsp8, involved in replication and transcription (13)(14)(15); several RNA modification enzymes, such as nsp14, an exoribonuclease, nsp15, an endoribonuclease, and nsp13, a helicase/RNA triphosphatase (16,17); and two S-adenosyl-L-methionine (AdoMet)-dependent methyltransferases carried by nsp14 (N7-MTase) and nsp16 (2ЈO-MTase) (18 -20). In addition, some of these nsps have thus far no known function nor enzymatic activity, and/or their functions remain more elusive (nsp1, nsp2, nsp4, nsp6, nsp9, nsp10, and nsp11), even if some of them may regulate host cellular functions (nsp1, nsp4, and nsp6) or enzymatic activities from the replication-transcription complex (10).…”
mentioning
confidence: 99%
“…Among these are the proteolytic activities endowed by nsp3 and nsp5, required to mature pp1a and pp1ab polyproteins into individual non-structural proteins (11,12); the RNA-dependent RNA polymerase by nsp12, and a putative RNA primase, nsp8, involved in replication and transcription (13)(14)(15); several RNA modification enzymes, such as nsp14, an exoribonuclease, nsp15, an endoribonuclease, and nsp13, a helicase/RNA triphosphatase (16,17); and two S-adenosyl-L-methionine (AdoMet)-dependent methyltransferases carried by nsp14 (N7-MTase) and nsp16 (2ЈO-MTase) (18 -20). In addition, some of these nsps have thus far no known function nor enzymatic activity, and/or their functions remain more elusive (nsp1, nsp2, nsp4, nsp6, nsp9, nsp10, and nsp11), even if some of them may regulate host cellular functions (nsp1, nsp4, and nsp6) or enzymatic activities from the replication-transcription complex (10).…”
mentioning
confidence: 99%
“…It has been proved that the severe onset of SARS epidemic in 2003 with over 800 fatalities was evoluted in a market of life-caged dogs market in China. Studies confirmed that caged animals and bats were the potential intermediate hosts [1,2].…”
Section: Introductionmentioning
confidence: 54%
“…Although this was most famously illustrated by the spread of SARS-CoV from Chinese horseshoe bats to human populations during the 2002-2003 epidemic, other coronaviruses such as HCoV-OC43 and bovine coronavirus (BCoV), or feline coronavirus-II, canine coronavirus-II and transmissible gastroenteritis virus(swine virus) are very closely related, consistent with cross-species transmission 19 . This ability to adapt to new environments raised concerns that MERS-CoV would gain virulence and enhanced ability to transmit from human-to-human as the MERS outbreak continued, but this has not occurred.…”
Section: Virology Of Mers-covmentioning
confidence: 95%